Effect of Rigid Gas Permeable Contact Lenses on Nystagmus and Visual Function in Hyperopic Patients with Infantile Nystagmus Syndrome. (2nd January 2017) - Bagheri, Abbas; Abbasi, Hamed; Tavakoli, Mehdi; Sheibanizadeh, Abdolreza; Kheiri, Bahareh; Yazdani, Shahin
ABSTRACT: Purpose : To determine the effect of rigid gas permeable contact lenses (RGPCL) on involuntary eye movements and visual function in hyperopic patients with infantile nystagmus syndrome. Methods : This prospective interventional case series was conducted on 16 patients with infantile nystagmus and hyperopia equal or more than +0.5 D and astigmatism more than -1 D over a 2-year period. A complete ophthalmological examination including determination of best corrected visual acuity (BCVA), contrast sensitivity, and videonystagmography was performed for all patients before and after at least 3 months of RGPCL use, and the outcomes were compared. Results : Thirty-two eyes of 16 patients with mean age of 18.6±4.9 years were enrolled. Mean spherical equivalent refractive error was +1.5±2.35 (range +1 to +6.25) diopters (D); corresponding values were +2.45±2.44 D (range +0.5 to +7.5) for spherical error and +1.90±0.83 D (range +1 to +4) for astigmatism. Monocular BCVA improved from 0.56±0.23 to 0.51±0.23 Log MAR ( P =0.007), and binocular BCVA improved from 0.54±0.25 to 0.48±0.24 Log MAR ( P =0.01) after fitting RGPCL. Following the use of RGPCL, contrast sensitivity was significantly improved at low ( P =0.02) and intermediate ( P < 0.001) frequencies but not at high frequencies ( P =0.6). The frequency, amplitude, and intensity of nystagmus were decreased significantly after RGPCL use ( P <0.001). Conclusion : RGPCL improved monocular and binocular BCVA and contrast sensitivity in hyperopic patients with infantile nystagmus syndrome. Motor indices of nystagmus (frequency, amplitude, and intensity) were also significantly improved after RGPCL use.